Cluster analysis of winds and wind-induced vibrations on a long-span bridge based on long-term field monitoring data. (1st May 2017) - Li, Shanwu; Laima, Shujin; Li, Hui
Highlights: Cluster analysis is proposed to recognize vortex-induced vibrations (VIVs) of bridge. The relationship between the wind speed field and VIV mode is obtained by cluster analysis. The nonuniformity of wind flow has a significant influence on the VIV mode. Abstract: In this study on a long-span suspension bridge, the wind and vibration data collected by a long-term monitoring system from the year 2010 to 2014 are used for cluster analysis. An automatic and fast clustering algorithm is employed to recognize the vortex-induced vibrations (VIVs) on the bridge deck in long-term monitoring datasets. The acceleration amplitude (root mean square) and frequency ratio are selected as indicators for the clustering of the VIVs from other vibrations. Cluster analysis is further conducted on the wind speed field of VIV samples, and the results indicate that the nonuniformity of the wind speed along the span-wise direction has a significant influence on the VIV mode. The relationship between the wind speed field and VIV mode is obtained by the clustering with consideration of nonuniformity of the wind speed.